Numerical simulation of pulverized coal MILD-oxy combustion under different oxygen concentrations. Issue 4 (August 2020) - Kuang, Yucheng; He, Boshu; Tong, Wenxiao; Wang, Chaojun; Song, Jingge; Ying, Zhaoping
Abstract: As an emerging clean coal combustion technology, Moderate or Intense Low-Oxygen Dilution (MILD) combustion or oxy-fuel combustion, compared with traditional coal combustion, has many advantages. However, compared with MILD combustion and oxy-fuel combustion, MILD-oxy combustion is believed more attractive. In this work, MILD-oxy combustion characteristics with oxygen concentrations from 10% to 50% are studied numerically. The results show that within a certain range, increasing the oxygen concentration is in favor of MILD-oxy combustion performance close to that of MILD-air combustion. When the oxygen concentration is higher enough, the momentum reduced by the increase of oxygen concentration has a great influence on the furnace temperature. With the increase of oxygen concentration, the radiation heat transfer is enhanced and the convective heat transfer is weakened. The increase of oxygen concentration can promote the occurrence of char gasification reaction with CO2 . In addition, MILD-oxy combustion has a large impact on CO emission. Highlights: Characteristics of the coal MILD-oxy combustion are simulated for 10%-50%O2 . Reducing O2 can improve MILD performance, but increasing O2 can reduce CO emission. The peak temperature during coal combustion increases with the O2 concentration. Increasing O2 concentration can promote the char gasification with CO2 and H2 O. For coal MILD-oxy combustion, CO emission is not negligible.